Appropriate management of Mirizzi syndrome. Literature review - Jorge Luis Estepa Pérez; Paolo Martini; Biagio Di Trani; Carmeni Picarelli; Angela Conti; Verónica Crocco (Medisur)
Mirizzi syndrome is a rare complication of gallstone disease, with an incidence of less than 1% in developed countries. It is characterized by extrinsic compression of the bile duct, produced by pressure applied indirectly by one or more stones embedded in the infundibulum of the gallbladder (Hartmann's pouch); As the inflammatory process progresses, obstruction, necrosis, and even internal biliary fistula may occur. Among the imaging study methods available for diagnosis are abdominal ultrasound, computed axial tomography, cholangioresonance and endoscopic retrograde cholangiography. Clinically, it represents a diagnostic challenge, not only because it is a rare condition, but also because of its non-specific presentation. The most used treatment is surgery, for the resection of the gallbladder and the extraction of the impacted stone, in order to achieve decompression of the bile duct and prevent recurrence. The purpose of this review is based on the need to recognize the existence of this disease, which is rare and sometimes goes unnoticed during the management of a patient with abdominal pain, which explains the high percentage of intraoperative diagnoses, resulting in a more problem for the surgeon